Two-stage electro-discharge machining fabricating superhard cutting tools - Mamalis, A. G.; Grabchenko, A. I.; Magazeev, M. G.; Krukova, N. V.; Prohàszká, J.; Vaxevanidis, N. M. (Elsevier Inc., 2004)
A novel technique for fabricating efficiently precision cutting tools made from polycrystalline superhard materials is reported in the present paper. For this purpose, a two-stage electro-discharge machining (EDM) was applied on diamond polycrystallines, by employing first wire-electrode EDM for rough cutting and subsequently rotational disc-electrode EDM for finishing operations. Experimental results obtained clearly indicate the applicability of the proposed two-stage technique for fabricating precision cutting tools that can be used for the production of machined components made from glass and plastics, ceramics, composite materials and non ferrous metals, at an industrial scale.
Keywords: electro-discharge machining; diamond polycrystallines; rotational disc-electrode; composite materials; non-ferrous metals; superhard materials; cutting tool